Religiøs ikonografi og politisk agitation - Carsten Riis (Religionsvidenskabeligt Tidsskrift, 1986)
About the painting “The Siege of Constantinople” as found on six churches from the 16th century in Moldavia. In the first decades of the 16th century the late Byzantine iconography flourished in Moldavia on church exteriors. On six churches within a radius of 30 kilometres are found a siege scene, “The Siege of Constantinople”, in connection with a painting of the Akathist Hymn. The article seeks the historical background of the painting in the siege of Constantinople by the Turkish army in 1453. In uncovers, through an interpretation of the painting from the Moldovita Monastery, the Moldavian painters’ knowledge of the fall of Constantinople. At the same time, this was the defeat of the centre of the Orthodox Church to which Moldavia belonged. From the connection with the Akathist Hymn and the explanatory text which follows the painting on the church in Arbore, the religious aspect of the paintings is connected to the Persian siege of Constantinople in 626, where an intervention by Virgin Mary was believed to have saved the city. During the Turkish pressure in the 1530’s, this tradition is moulded into an anti-Turkish ideological manifest in Moldavia. This takes place by altering the historical scene for the events in 626, and in this manner the situation of Moldovia is incorporated into the paintings. The church of Arbore has been painted as the last one and has an account which varies in considerable degree from the five others regarding the historical aspect, because at that time Turkish control of the area increased. However, its religious aspect is still Christian and anti-Turkish. After 1541 the picture is no longer painted, probably because of even stronger Turkish control.